The genus Neotrichia Morton 1905 (Trichoptera: Hydroptilidae) in Pará state, Northern Brazil: New species and an unpublished species made available - Neto, Jaime De Liege Gama; Ribeiro, José Moacir Ferreira; Passos, Mahedy Araujo Bastos (Zootaxa, 2021)
Five new species of Neotrichia Morton 1905 from Brazil are described, including Neotrichia dirrocha sp. nov., N. jamevu sp. nov., N. paidegua sp. nov., N. pavula sp. nov., and N. flinti Keth sp. nov. Among these, N. flinti Keth sp. nov., a species described by Keth (2002) from Venezuela but not previously published, is made available. Illustrations of male genitalia are provided with each description.